Multi-projector VR Systems - Soares, L. P.; Jorge, J.; Dias, M.; Raposo, A.; Araujo, B.; Carvalho, F. (2010 23RD SIBGRAPI - Conference on Graphics, Patterns and Images Tutorials, 2010)
Immersive multi-projection environments are becoming affordable for many research centers, but these solutions needs several integration steps to be fully operational, and some of these steps are difficult and not in a common domain. This paper presents the most recent techniques involved in multi-projection solutions, from projection to computer cluster software. The hardware in these VR (Virtual Reality) installations is a connection of projectors, screen, speaker, computers and tracking devices. This survey paper will introduce hardware options, explaining their advantages and disadvantages. We will cover software design and open source tools available, and how to administrate the whole solution.